Modern marketing features of freight transportation on Ukrainian market terms - Radionova, N. V.; Kobets, O. I. (Science and Transport Progress, 2011)
In the article the issue on searching methods of use of marketing tools for resolving the railway transport development problems and functioning this branch in the market conditions is considered.